ERα-Targeting PROTAC as a Chemical Knockdown Tool to Investigate the Estrogen Receptor Function in Rat Menopausal Arthritis - Duan, Li; Xu, Xiao; Xu, Limei; Wen, Caining; Ouyang, Kan; Li, Zigang; Liang, Yujie (Frontiers in Pharmacology, 2021)
Proteolytic targeting chimeras (PROTACs) is a rapid and reversible chemical knockout method. Compared with traditional gene-editing tools, it can avoid potential genetic compensation, misunderstandings caused by spontaneous mutations, or gene knockouts that lead to embryonic death. To study the role of estrogen receptor alpha (ERα) in the occurrence and progression of menopausal arthritis, we report a chemical knockout strategy in which stable peptide-based (PROTACs) against ERα to inhibit their function. This chemical knockdown strategy can effectively and quickly inhibit ERα protein in vivo and in vitro. In the rat menopausal arthritis model, this study showed that inhibiting estrogen function by degrading ERα can significantly interfere with cartilage matrix metabolism and cause menopausal arthritis by up-regulating matrix metalloproteinase (MMP-13). The results of this study indicate that ERα is a crucial estrogen receptor for maintaining cartilage metabolism. Inhibition of ERα function by PROTACs can promote the progression of osteoarthritis.